Cambridge Primary English Learner's Book - 3 - Gill Budgell; Kate Ruttle (Cambridge, United Kingdom CAMBRIDGE UNIVERSITY PRESS, 2014)
Cambridge Primary English is a flexible, endorsed course written specifically to support Cambridge International Examinations' curriculum framework (Stages 1-6). The resources are aimed at first language English learners, encouraging them to actively explore, use and apply their core listening, speaking, reading and writing skills through individual, pair and group work. Engaging activities provide opportunities for differentiated learning and promote creativity and critical thinking. Lively international fiction, non-fiction and poetry texts are the basis for teaching reading and writing skills, including comprehension, grammar, punctuation, phonics, spelling and handwriting. Learners also practise their spoken English to build vocabulary and confidence through class and group discussion. Each stage contains three core components (Learner's Book, Activity Book, and Teacher's Resource Book with accompanying CD-ROM) which are fully integrated and offer a complete show more
Keywords: TR PY Language -- TR PY Language